2020
DOI: 10.1536/ihj.19-231
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sacrubitril/Valsartan on Clinical Treatment and hs-cTnT and NT-ProBNP Serum Levels and the Left Ventricular Function in Patients with Chronic Heart Failure

Abstract: Chronic heart failure (CHF) seriously affects the quality of patients' lives. Sacrubitril/valsartan is a combination angiotensin receptor-neprilysin inhibitor, a new therapeutic drugs to treat CHF. This study aims to observe the impact of sacrubitril/valsartan on clinical treatment and high-sensitivity cardiac troponin T (hs-cTnT), N-terminal pro-brain natriuretic peptide (NT-ProBNP) serum levels, the improvement of the left atrial diameter (LAD) and left ventricular end diastolic dimension (LVEDD), and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Five RCTs reported renal function as primary or secondary outcome of interest, 11,14,18,20,28 while the remaining five RCTs only reported it as adverse event 24–27,29 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five RCTs reported renal function as primary or secondary outcome of interest, 11,14,18,20,28 while the remaining five RCTs only reported it as adverse event 24–27,29 …”
Section: Resultsmentioning
confidence: 99%
“…The study selection process is described in Figure . Among the initial 3483 records, 10 studies published between 2012 and 2019 met our inclusion criteria for a total of 16 456 subjects 11,14,18,20,24–29 . The mean age across the studies ranged from 57.6 to 72.7 years, and 10 949 (66.5%) participants were men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can only speculate that the increase in mechanical stress associated with the prolonged systolic time may have induced a strain promoting membrane fragility in compromised cardiac myocytes. In contrast, using a hs-cTnT antibody, Packer et al and Gao et al [90,91] reported an improvement in function and a decrease in serum cTnT in chronic heart failure patients treated with angiotensin/neprilysiin inhibition. The initial trial testing Omecamtiv is in the process of being significantly expanded (GACTIC-HF) with an end point of improving clinical outcomes [92].…”
Section: Serum Ctni and Ctni Levels And Inotropic Interventionsmentioning
confidence: 96%